Preliminary results of the histological bone study of maastrichtian bird remains from Marambio Island - Talevi, Marianella (2020)
Fil: Talevi, Marianella. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.